Ischaemic stroke, preventable with tissue adhesive - Pieter Bothma; Goncalo Campos; Ananda Shakya (European Journal of Case Reports in Internal Medicine, 2023)
LETTER TO THE EDITOR This Letter comments on the following case report: Abu-Abaa M, Dawood G, Arshad H, Mousa A, Jumaah O. Acute ischaemic stroke by a different mechanism. EJCRIM 2022;9:doi:10.12890/2022_003618.